Improving voluntary public good provision through a non-governmental, endogenous matching mechanism: experimental evidence - Reif, Christiane; Rübbelke, Dirk T. G.; Löschel, Andreas (Environmental and resource economics, 2017)
Social norms can help to foster cooperation and to overcome the free-rider problem in the private provision of public goods. This paper focuses on the endogenous establishment of an average-oriented norm which sanctions deviations from average public good contributions. In a laboratory experiment, we analyse whether subjects are willing to implement a punishment and reward scheme at their own expense by applying the theory of non-governmental norm enforcement put forward by Buchholz et al. (J Public Econ Theory 16(6):899-916, 2014). Based on their theory, which omits a central authority but introduces an endogenously determined enforcement mechanism, we implement a two-stage public good game. In the first stage, subjects determine the strength of the sanctioning mechanism on their own. In the second stage, they decide on their personal contributions to the public good based on the established mechanism. In line with comparable pool punishment experiments, we find that subjects are apparently willing to contribute funds in order to establish a norm enforcement mechanism. Groups over-invest in the mechanism, but this over-investment decreases over time. These investments seem to be driven by the subjects’ previous individual contributions and partly by a number of strategic considerations, i.e. the previous average contribution made to the public good lowers the investment in the sanctioning mechanism. In the second stage of our experiment, higher norm enforcement parameters tend to lead to higher public good contributions. The earnings with the mechanism are on average higher than without.